2014
DOI: 10.1093/deafed/enu029
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Parent Support Provided by Parent Mentors for Families With Deaf/Hard-of-Hearing Children: Voices From the Start

Abstract: This study used a qualitative design to explore parent mentors' summaries of conversations with more than 1,000 individual families of deaf and hard-of-hearing (DHH) children receiving parent-to-parent support as part of an existing family support project. Approximately 35% of the families were Spanish speaking. Five parent mentors who have DHH children provided varied support primarily via the telephone to families with DHH children, frequently birth to age 3. The nature and types of support provided were exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
2
8
0
2
Order By: Relevance
“…The parent-to-parent support allows parents to identify the reality of what it is like to have a child who is deaf and hard of hearing and address how parents can make decisions regarding intervention. This may reduce delays in that parents may not try out all available options before making an informed decision, for example, regarding communication options, schooling and rehabilitative methodologies (Narr & Kemmery, 2015 ). According to Lederberg and Golbach ( 2002 ), you need to be a parent of a deaf or hard of hearing child to comprehend the depth of parenting a deaf or hard of hearing child.…”
Section: Discussionmentioning
confidence: 99%
“…The parent-to-parent support allows parents to identify the reality of what it is like to have a child who is deaf and hard of hearing and address how parents can make decisions regarding intervention. This may reduce delays in that parents may not try out all available options before making an informed decision, for example, regarding communication options, schooling and rehabilitative methodologies (Narr & Kemmery, 2015 ). According to Lederberg and Golbach ( 2002 ), you need to be a parent of a deaf or hard of hearing child to comprehend the depth of parenting a deaf or hard of hearing child.…”
Section: Discussionmentioning
confidence: 99%
“…The spouses' role of encouraging their partners to engage actively poses positive effects to the children's speech development. Spouses' supports are usually inconsistent, but still relevant to the children's best interest [11,20].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, parents positively rated most HRQoL domains, although education and the effects of implantation received significantly fewer positive ratings (Kumar, Warner-Czyz, Silver, Loy, & Tobey, 2015). Other parents within the parenting styles paradigm advocated rational information sessions with language specialists for developing parent-significant theoretical knowledge (Veland, Bru, & Idsøe, 2014;Narr & Kemmery, 2015). Later studies demonstrated wide-ranging findings.…”
Section: Family Qol Of Families Raising Children With Cis or Hasmentioning
confidence: 99%
“…Overall, the researchers encouraged a line of research on parent mentoring. For example, parents trained by PTs should provide what is necessary for understanding and responding to the children's multiple disabilities and hearing-related topics (Narr & Kemmery, 2015).…”
Section: Study Limitations and Recommendations For Further Researchmentioning
confidence: 99%